PENGARUH PENDAPATAN ASLI DAERAH (PAD), BELANJA DAERAH, ANGKATAN KERJA, KEMISKINAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA PADA PERIODE 2017–2020 - Elin Awanta Rajagukguk (Fakultas Ekonomi Prodi Akuntansi, 2021)
ABSTRACT This observation is useful in examining how the impact of Original Local Government Revenue, Expenditure, Labor Force, and Poverty on the Gross Regional Domestic Product (GRDP). The data used in the form of publication information for the Province of North Sumatra in Figures 2021 every year is published on the BPS website for the Province of North Sumatra.. The sampling method is taken from saturated sampling. The test method uses multiple linear regression, and classical assumption tests, namely normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, T test, F test and coefficient test (R2). The test results in this study are (1) Original Local Government Revenue does not have a significant impact on Gross Regional Domestic Product. (2) Expenditures have a significant negative effect on Gross Regional Domestic Product. (3) Labor force and poverty have a positive and significant effect on Gross Regional Domestic Product. (4) Original Local Government Revenue, Expenditure, Labor Force and Poverty have a simultaneous impact on Gross Regional Domestic Product. By obtaining the Ajuted Rsquare value of 37.3% and the result of 62.7 is the remaining influence of other variables or other factors. Keywords: OLGR, Expenditure, Labor Force, Povert, GRDP